Carbon nanotube memory cell array program error analysis and tradeoff between reset voltage and verify pulses. (24th February 2016) - Ning, Sheyang; Iwasaki, Tomoko Ogura; Hachiya, Shogo; Rosendale, Glen; Manning, Monte; Viviani, Darlene; Rueckes, Thomas; Takeuchi, Ken
Abstract: In emerging non-volatile memories, nano-random access memory (NRAM) has advantages of small program current and high endurance compared with resistive RAM (ReRAM) and phase-change RAM (PRAM). This work comprehensively investigates NRAM set and reset program characteristics by measuring a 116 nm 4 Mbit NRAM cell array. Specifically, reset is found more dependent on reset voltage than reset current. Next, NRAM set and reset bit error rates (BERs) have less significant reduction compared with the increased ratio of set and reset pulse widths. The reset BER can also be reduced by applying multiple reset pulses. Moreover, 10 8 write cycles are measured on 256 bytes NRAM cells, no wear-out or broken cell is found. Finally, the program characteristics of two verify-reset schemes are compared. The maximum verify-reset voltage can be reduced by increasing the number of reset pulses.